Emerging roles of the renin‐angiotensin system in select oral diseases - Liu, Yixing; Liu, Zhe (Oral diseases, 2025)
Objectives The renin‐angiotensin system (RAS) plays essential roles in cardiovascular and renal function regulation. Recent studies have shown that the RAS components are widely expressed in oral tissues, but their roles in oral diseases remain underexplored. This review aims to summarize the effects of the RAS in select oral diseases including oral squamous cells carcinoma (OSCC), periodontitis, oral submucous fibrosis (OSF), and ageusia/dysgeusia. Subjects and Methods Data searches were performed using PubMed, Web of Science and Scopus through July 2024. A narrative overview of current literature was undertaken to synthesize the contexts with elaboration and summary. Results In OSCC, ACE/Ang II/AT1R promotes OSCC by inducing angiogenesis, cell proliferation and invasiveness. Conversely, ACE/Ang II/AT2R and ACE2/Ang (1–7)/MasR inhibit OSCC progressions. In periodontitis, ACE/Ang II/AT1R upregulates inflammatory cytokines and promotes osteoclast differentiation factor RANKL, whereas ACE2/Ang (1–7)/MasR exerts opposite effects by preventing inflammation and alveolar bone loss. In OSF, Ang (1–7) counters the profibrotic and proinflammatory action of Ang II. In dysgeusia, Ang II suppresses salt taste responses and enhances sweet taste sensitivities, while Ang (1–7) exhibits opposite effects. Conclusions The RAS cascade plays crucial roles in OSCC, periodontitis, OSF and ageusia/dysgeusia. The imbalanced RAS may aggravate the progression of these diseases.